Choice of Subject as Carrier by Medical Students in Pakistan (Medical Forum Monthly, 2024)
Objective: To find out the preference of medical students in Pakistan.Study Design: Observational / descriptive / cross-sectional studyPlace and Duration of Study: This study was conducted at Avicenna Medical College from January 2016 to March 2016.Materials and Methods: All the 2nd year students were included in the study. They were asked to fill a self-designed questionnaire in which along the demographic details, they were to mention the field which they want to continue for specialization. Also they were to mention the reason for opting that specialty.Results: A total of 105 students participated in the study. The mean age of participants was calculated as 21.75±3.68 years. There were 73 (69.5%) females while 32 (30.5%) male participants. The most commonly opted field was clinical sciences and among them surgery was selected by most of the participants. The most common reason for opting particular specialty was interest of the students.Conclusion: We conclude that interest of our medical students into basic medical sciences is less than clinical sciences. We need to identify the factors and take certain measures so that more students could opt basic sciences also as their career